Sustainability, Capital Structure, and Growth on Firm Value: Evidence from the Indonesian Technology Sector with Profitability and ERM as Moderators - Arief Syafrudin; Asep Risman (Dinasti Publisher, 2026)
This study aims to examine the effect of Sustainability, Capital Structure, and Firm Growth on Firm Value, with Profitability and Enterprise Risk Management as moderating variables in technology sector companies listed on the Indonesia Stock Exchange during 2019–2024. The population consists of 47 companies, with a sample of 14 firms selected through purposive sampling. The study uses secondary data obtained from financial statements and annual reports published on the official website of the Indonesia Stock Exchange and company websites. The analytical methods employed are panel data regression and Moderated Regression Analysis using the Random Effect Model approach. The findings reveal that Capital Structure and Firm Growth have a positive and significant effect on Firm Value, while Sustainability has no significant effect. Profitability does not moderate the relationships between Sustainability, Capital Structure, and Firm Growth and Firm Value. Enterprise Risk Management does not moderate the effect of Sustainability and Firm Growth; however, it strengthens the positive effect of Capital Structure on Firm Value. Simultaneously, the model is statistically significant with an explanatory power of 30.22 percent. These results indicate that financing decisions and growth performance are more valued by the market when supported by effective risk management practices